Ionic Liquid Aided [11C]CO Fixation for Synthesis of 11C‐carbonyls - Anton Lindberg; Narges Mokhtarinori; Zhenzhen Yang; Sheng Dai; Ilja Popovs; Neil Vasdev (ChemistryOpen)
Abstract Tributyl(ethyl)phosphonium oxopentenolate ([P4442][Pen]) is an ionic liquid developed to capture CO and has shown ability to catalyze carbonylation reactions in organic chemistry. Carbon‐11 (11C, t1/2=20.4 min) labeled CO is a highly versatile building block for the synthesis of positron emission tomography (PET) radiotracers that are applied for medical imaging. The use of [11C]CO is limited by its low solubility in organic solvents. Herein, we report a proof‐of‐concept study evaluating a new method to prepare 11C‐labeled amides, ureas and carbamates via reaction of [11C]CO in [P4442][Pen] and applied for fully automated radiosyntheses of Bruton's tyrosine kinase inhibitors, [11C]evobrutinib and [11C]ibrutinib.